Every missing piece - Conklin, Melanie (Little, Brown and Company, 2022)
After her father died in a tragic accident, Maddy Gaines sees danger everywhere, fueled by buried anxiety. Her distress is further heightened by a new stepfather and changes in her best friend. When she sees a boy named Eric setting up booby traps in the woods, she's convinced he's a boy that went missing six months ago and begins to gather evidence in order to convince her mother and the local police.